Partisipasi Masyarakat Desa Bekiung sebagai Kontrol Sosial dalam Pengelolaan Dana Desa Berdasarkan Pasal 68 Ayat 1 UU No. 3 Tahun 2024 - Gracia Feby Yeski Sitepu; Parlaungan Gabriel Siahaan (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze community participation as a form of social control in the management of village funds in Bekiung Village based on Article 68 Paragraph (1) of Law No. 3 of 2024, as well as the access to information received by the community. The study employs a normative-empirical legal method with statutory and conceptual approaches, using descriptive qualitative analysis. The results indicate that community participation is not yet optimal due to limited understanding, the dominance of individual interests, and restricted information dissemination. Participation is more prominent in the physical implementation stage. Information regarding village fund management remains limited, resulting in uneven transparency.